DAMPAK KEBIJAKAN FISKAL TERHADAP OUTPUT DAN INFLASI - Syahputra sinaga; Yenni sampri juliaty nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research analyzes the impact of fiscal policy on output and inflation in a microeconomic context. Through a quantitative approach, we use econometric models to evaluate the response of economic sectors' output and inflation rates to changes in fiscal policy. Our findings reveal that fiscal policy has a significant influence on economic growth and inflation rates. These results provide important insights for policy makers to optimize fiscal policy to achieve a sustainable balance between economic growth and price stability. The empirical results show that there is a cointegration relationship between government spending and taxes on output in the long run. In the long term, taxation has a positive impact on economic growth while government spending does not. Short-run adjustments show that the shock of increasing government spending has a positive impact on output while the shock of increasing taxes has a negative impact. The more dominant influence of government spending on output in the short term compared to taxes shows that this policy is still quite effective in stimulating economic growth, especially during a recession. Meanwhile, an increase in government spending causes a decrease in inflation, while an increase in taxes causes an increase in inflation. This study also shows that there is no fiscal policy discretion carried out by the government.